Efeito clínico do plasma rico em plaquetas em lesões cutâneas, tendíneas e ligamentares de equinos - Pereira, Roberta Carneiro da Fontoura (2016)
Platelet rich plasma (PRP) is a product obtained from whole blood through one or two centrifugations, resulting in small volume of plasma containing high number of platelets and growth factors. The growth factors from the α-granules are platelet components that are important in the homeostasis of injured tissues beginning and regulating some stages of tissue healing, promoting chemotaxis, cell proliferation and differentiation, neovascularization and deposition of extracellular matrix. Wound healing of skin lesions distal to the carpus or tarsus of horses, usually are complicated by the reduced blood supply, low oxygen tension and increased risk of bacterial contamination. In many cases when wounds are not treated properly, they can become chronic with excessive formation of granulation tissue. Tendinitis and desmites are pathologies characterized by degeneration of tendons and ligaments. The tissue degeneration mechanism of these structures is attributed to mechanical factors, vascular and inflammatory. Tendinitis and desmitis are common pathologies of equine athletes, these diseases tend to have long recovery periods, due to histological, anatomic and biomechanical features of tendons and ligaments. This thesis presents studies of 8 horses, in order to evaluate the clinical effect and the presence of recurrence lesions, of use of PRP and exercise controlled in the treatment of tendon and ligament injuries, through the clinical and ultrasonographic evaluation (CHAPTER 1), review by clinical and histopathological evolution the healing process of surgical wounds located at the distal region of forelimbs treated by three different methods of application of PRP (CHAPTER 2), and also determine the best form to PRP application to equine skin wounds ( CHAPTER 2.) In Chapter 1, it included eight horses, with an average age of 5 years (± 2.6) diagnosed with injuries in tendons and ligaments, through clinical and ultrasonographic evaluation. These animals underwent treatment with intralesional PRP, guided by ultrasound. The animals μL diagnosed with tendonitis (4/8) had lesion scores of 2.3 (± 0.57) (score 1 to 3), mean platelet concentration of 512.250 / uL (± 144.965) and average healing time of 262 days (± 82) (Table 2). In contrast, animals with desmitis (4/8) in the suspensory ligament injuries had a score of 2.6 (± 0.57) (score 1 to 3), mean platelet concentration of 566.500 / uL (± 97.722) and average healing time 120 days (± 42) (table 3). In this study no correlation was found between the number of platelets in the PRP, and the time for healing of tendonitis and desmitis. Clinical and ultrasonographic monitoring of intralesional injections of PRP, followed by gradual increase of exercise program, allowed the horses to return to his previous athletic activity without recurrence of the lesions. In Chapter 2 we used eight healthy horses, with an average age of 8 years (± 3.76), which were created four wounds of 4 cm2 area in the dorsolateral aspect of the third cannon bone, two on the left forelimb (A1 and A2) and two on the right forelimb (A3 and A4) (figure 1). The cutaneous lesions were treated according to the established treatment group. In the same animal, each of the four wounds were assigned to one of four treatment groups at random, for each treatment group obtained eight replicates in different regions in the forelimbs (Figure 1). In the group (G) I, the skin lesions were treated with PRP infiltration of the wound edges, the GII PRP was used in gel form, the GIII was used homologous PRP and GIV as a control group (without PRP application). In the wounds treated with the GII was reduced to a fortnight in healing time compared the wounds treated with the GIV. Histopathology GII presented a higher frequency of mild inflammation and neovascularization mild to moderate in biopsies 1 and 2. The GIV had the highest intensity of granulating wounds between the groups. PRP in gel form, both in the clinical evaluation as the histopathology showed the best result in the application on wounds in the distal member of horses. The homologous PRP can also be used as adjuvant in equine wound healing.